Creating Resilient Artificial Intelligence Systems. A Responsible Approach to Cybersecurity Risks - Bierecki, Dominik; Gaie, Christophe; Karpiuk, Mirosław; Langlois-Berthelot, Jean (PRAWO i WIĘŹ, 2025)
In a computerised state, where the information society makes extensive use of digital services, artificial intelligence is important. To facilitate the use of cyberspace, AI systems needed to be resilient to cyber threats that can not only limit the operation of such systems, but also take control of them. Ensuring cyber security requires the introduction and use of appropriate protective measures, both at the stage of creating such systems, implementing them and using them. It should be emphasized that the use of new technologies, including artificial intelligence, must be done responsibly, so as not to expose oneself and other users to risks, including those that cause significant damage. The authors use the dogmatic-legal method, through which an analysis was made of legal acts that normalise both artificial intelligence and cyber security issues. The theoretical-legal method was used to analyse the literature on both normative issues related to artificial intelligence and its potential, as well as obligations related to cyber security, including countering threats occurring in cyberspace.